Implementation of a Smart Home Intruder Detection System using a Vibrometer and ESP 32 CAM - Samuel Owoeye; Folasade Durodola; Adekunle Oyelami; Racheal Oladejo; Samuel Obasuyi; Ademola Qasim; Joshua Ogundairo (ABUAD Journal of Engineering Research and Development)
Nigeria today is rife with occurrences of intruders breaking into homes at every slight opportunity. The topic of security is quite important; hence this paper presents the development and implementation of a Smart Intruder Detection System utilizing the ESP32-CAM board, the Vibrometer and the ATMega328P microcontroller to enhance lighting, security, and surveillance functionalities. The ESP32-CAM serves as the central control unit, leveraging its built-in Wi-Fi and camera capabilities, while communicating with the ATMega328P microcontroller responsible for managing lighting, security, and surveillance components. The Vibrometer adds a vital layer of security by detecting vibrations associated with forced entry attempts. Upon sensing significant vibrations, the Vibrometer triggers the ESP32-CAM to start an immediate recording of potential intrusions. In the realm of lighting control, the ATMega328P regulates diverse light sources such as LEDs and smart bulbs. The ESP32-CAM facilitates a user-friendly experience, enabling seamless control and automation of the lighting system through a dedicated mobile application or voice commands. For surveillance purposes, the ESP32-CAM captures real-time video, streaming it to the user's mobile device or a centralized monitoring station. The ATMega328P contributes to the system's intelligence by supporting motion detection algorithms, which, in turn, trigger automated alerts and activate lighting or alarm systems in response to detected movement. The precision performance of the components was carried out and the average precision for all the components was 95%.  The synergistic integration of the ESP32-CAM board and ATMega328P microcontroller results in a cohesive and intelligent smart home automation solution.